THE USING OF DIFFERENT EXTRACTION TIMESON THE ANTIOXIDANT ACTIVITY OF SEA CUCUMBER (Paracaudina australis) WITH FRAP METHOD - Putri, Dea Arsifah; Sukmiwati, Mery; Karnila, Rahman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract               This study aimed to determine the effect of different extraction times on the antioxidant activity of Sea Cucumbers (Paracaudina australis). The used methode was an experimental method with a completely randomized concoctions design (CRD). Consisting of 3 treatments levels namely T2(extraction time for 48 hours), T3(extraction time for 72 hours), T4(extraction time for 96 hours). This research consisted of 2 stages, namely 1) preparation of  sea cucumber raw materials, 2) Extraction by maceration method of sea cucumber flour. The tested parameters were yield, identification of secondary metabolites (phytochemicals) and antioxidant activity test of sea cucumber concentrates. The results showed that the amount of sea cucumber  concentrate produced with extractions times had different amounts, namely as follows: T47.90%, T37.46% and T27.29%. The most optimal maceration time to obtain concentrate was T4(7.90%). The results showed that the secondary metabolites on Sea Cucumbers  included steroids, saponins, alkaloids, phenolics and flavonoids. Keywords: Antioxidants, Extractions, Sea Cucumbers, Secondary Metabolites.